2015
DOI: 10.1099/ijsem.0.000476
|View full text |Cite
|
Sign up to set email alerts
|

Ursidibacter maritimus gen. nov., sp. nov. and Ursidibacter arcticus sp. nov., two new members of the family Pasteurellaceae isolated from the oral cavity of bears

Abstract: Thirty-three suspected strains of the family Pasteurellaceae isolated from the oral cavity of polar and brown bears were characterized by genotypic and phenotypic tests. Phylogenetic analysis of partial 16S rRNA gene and rpoB sequences showed that the investigated isolates formed two closely related monophyletic groups, representing two novel species of a new genus. Based on 16S rRNA gene sequence comparison Bibersteinia trehalosi was the closest related species with a validly published name, with 95.4 % simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…The PM shared 60% sequence similarity with G. parasuis in epitope 5D11, having six different amino acids at P 325 , Q 326 , E 328 , N 330 , L 331 , and A 336 . Among them, Nicoletella and Mannheimia mainly infected horses [20], cattle [21] and sheep [22], and Ursidibacter from the bear mouth [23]. However, Actinobacillus indolicus [29], APP [30], and PM [31] can infect pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PM shared 60% sequence similarity with G. parasuis in epitope 5D11, having six different amino acids at P 325 , Q 326 , E 328 , N 330 , L 331 , and A 336 . Among them, Nicoletella and Mannheimia mainly infected horses [20], cattle [21] and sheep [22], and Ursidibacter from the bear mouth [23]. However, Actinobacillus indolicus [29], APP [30], and PM [31] can infect pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the results revealed that Nicoletella semolina, Mannheimia haemolytica, Mannheimia pernigra, Ursidibacter maritimus, Ursidibacter arcticus, and Actinobacillus indolicus, share high sequence similarity in the position of epitope 5D11. Among them, Nicoletella and Mannheimia mainly infected horses [20], cattle [21] and sheep [22], and Ursidibacter from the bear mouth [23]. The APP shares 80% sequence similarity with G. parasuis in epitope 5D11, having three different amino acids at P 325 , N 330 , and A 336 .…”
Section: Alignment Analysismentioning
confidence: 99%